1996
DOI: 10.3109/13816819609057890
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented ocular fundus lesions and APC mutations in familial adenomatous polyposis

Abstract: Background Familial adenomatous polyposis (FA P) results from a germline mutation in the adenomatous polypsis coli (APC) gene on chromosome 5q21. The extracolonic manifestations of FAP include pigmented ocular fundus lesions (POF LS), cutaneous cysts, osteomas, occult radio-opaque jaw lesions, odontomas, desmoids, and extracolonic cancers. P O F L S are present at birth in about 80% of patients with F A P and are excellent clinical congenital markers for the disease. We studied the distribution of POFLS by num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…Mutations in the first eight exons of the gene result in polyposis in the absence of POFLs, whereas mutations in exons 9-15 are associated with polyposis and concomitant expression of POFLs. 13,14 In summary, the various forms of CHRPE can be distinguished from the POFLs based upon their characteristic clinical features. The ophthalmologist assumes an important role in differentiating the two entities.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the first eight exons of the gene result in polyposis in the absence of POFLs, whereas mutations in exons 9-15 are associated with polyposis and concomitant expression of POFLs. 13,14 In summary, the various forms of CHRPE can be distinguished from the POFLs based upon their characteristic clinical features. The ophthalmologist assumes an important role in differentiating the two entities.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristic fundus lesions are thought to occur in up to 80% of patients with APC mutation. 5 They may be present at birth, with no malignant potential. 5 We found one such lesion in each eye of our patient.…”
Section: Discussionmentioning
confidence: 99%
“…5 They may be present at birth, with no malignant potential. 5 We found one such lesion in each eye of our patient. Traboulsi and colleagues 6 demonstrated that multiple patches of pigmented ocular fundus lesions are a clinically useful predictor of colorectal polyposis.…”
Section: Discussionmentioning
confidence: 99%
“…There is a thickening of Bruch's membrane under the focal lesions. Mutations in exons 1-8 are associated with a POFL-negative phenotype, whereas those in exons 10-15 are generally associated with a POFL-positive phenotype [65][66][67]. These authors also proposed that POFLs are best classified as adenomas of the RPE.…”
Section: Pigmented Ocular Fundus Lesions Of Familial Adenomatous Polymentioning
confidence: 99%